POPULATION STRUCTURE AND BIOMETRIC RELATIONSHIPS OF Callinectes amnicola FROM THE CROSS RIVER ESTUARY, NIGERIA - UDOH, J. P; HOLZLOHNER, S.; EKANEM, S. B. (Nigerian Journal of Fisheries, 2011)
The population structure, carapace length-weight, carapace width- weight, carapace length-width parameters and condition indices of 262 specimens of Callinectes amnicola from the Cross River Estuary, Nigeria, were estimated for males, females and combined sexes. The results indicate that sex ratio was in favour of females (1:3.05,  2 = 67.26, 1df). Females were significantly heavier than males ( 2 = 12.15, 1 df, P < 0.05) but not significantly longer. Weight was found to be isometric with carapace length (b = 2.37) while carapace width-weight was negatively allometric (b = 2.17), indicating that the crabs get thinner with increase in width. The carapace length - width relationship showed b is < 3.0, indicating negative allometric growth pattern. Mean values of condition factors were higher in males than females suggesting males had a better condition during the study period. Average growth rate of C. amnicola in the estuary was estimated as 3.0 - 7.5 mm CL/month (smaller crabs grew faster).